What proportion of congenital abnormalities can be prevented?. Issue 6876 (20th February 1993) - Czeizel, A E; Intôdy, Z; Modell, B
Abstract : OBJECTIVE–To estimate the proportion of preventable congenital abnormalities in Hungary. DESIGN–Analysis of available Hungarian data-bases and of the effectiveness of primary, secondary, and tertiary preventive methods. SETTING–Databases of ad hoc epidemiological studies and of the Hungarian congenital abnormality registry. MAIN OUTCOME MEASURES–Prevalence at birth and prevalence after prevention in 73 congenital abnormality types or groups. RESULTS–Preventive methods are available for 51 (70%) of the 73 congenital abnormality types or groups evaluated. The birth prevalence of all congenital abnormalities could be reduced from 65 to 26 per 1000; thus 39 per 1000 (60%) are preventable. Without congenital dislocation of the hip, which is unusually common in Hungary, the preventable proportion of congenital abnormalities is 52%. CONCLUSION–Many congenital abnormalities can be prevented, but as they do not represent a single pathological category there is no single strategy for their prevention.